Voyages Short Narratives of Susanna Moodie - Moodie, Susanna (Canadian Short Story Library, 1997)
Susanna Moodie is, of course, best known for her books Roughing It in the Bush and Life in the Clearings, which are largely comprised of short sketches that she had previously published. What is not widely known, however, is that Moodie had a long and prolific literary career in which short sketches and tales were among her favoured genres. This book offers a selection of these narratives, most of which have been unavailable in print since the 19th century. This collection will give the reader a new understanding of Susanna Moodie's work.